THE EFFECTIVENESS OF INDUCTIVE TEACHING METHOD IN TEACHING PASSIVE VOICE FOR HIGH SCHOOL STUDENTS - Kaisar Zulfikar; Regina Sutapa; Y. Gatot Sutapa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aimed to investigate the effect of using the inductive teaching method on passive voice instruction. This research was designed in form of quasi-experimental research. The population of this research comprised the whole classes of eleventh grade students and two classes were chosen as sample for the study. Measurement technique was employed to find out if inductive teaching is effective or not for passive voice instruction. A set of multiple choice test was administered to experimental and control groups. This study revealed certain positive results. Firstly, the inductive teaching method is effective for teaching senior high school students, especially for teaching grammar. Secondly, Inductive Teaching method can help the students to acquire a better comprehension concerning the concept of passive voice, because Inductive teaching method assist the students to improve their ability to reason. In conclusion, inductive teaching method is a good option to be implemented in passive voice instruction, and grammar teaching in broader context. In addition, the researcher would like to suggest fellow teachers to implement inductive teaching method for grammar instruction since this method is suitable for today’s language teaching demands and focus on communicative aspect. Keywords: Effectiveness, Inductive Instruction and Deductive Instruction, Passive Voice.